1992
DOI: 10.1128/iai.60.12.5164-5171.1992
|View full text |Cite
|
Sign up to set email alerts
|

Early pathogenesis of infection in the liver with the facultative intracellular bacteria Listeria monocytogenes, Francisella tularensis, and Salmonella typhimurium involves lysis of infected hepatocytes by leukocytes

Abstract: The results show that Listeria monocytogenes, Francisella tularensis, and Salmonella typhimurium are facultative intracellular bacteria with a capacity to invade and grow in nonphagocytic cells in vivo. In the liver, all of these pathogens were seen to invade and to multiply extensively in hepatocytes. In all three cases, inflammatory phagocytes were rapidly marshalled to foci of infection where they appeared to cause the destruction of infected hepatocytes, thereby releasing bacteria into the extracellular sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(123 citation statements)
references
References 31 publications
6
115
1
1
Order By: Relevance
“…One theory is that the neutrophils function principally to lyse infected hepatocytes. This hypothesis, however, is based largely on electron micrograph images of neutrophils in contact with infected, but not uninfected, hepatocytes undergoing dissolution (18,49,52). In contrast to these data, other studies support the hypothesis that neutrophils mediate resistance to Listeria independently of direct hepatocyte lysis.…”
Section: Neutrophilsmentioning
confidence: 87%
See 1 more Smart Citation
“…One theory is that the neutrophils function principally to lyse infected hepatocytes. This hypothesis, however, is based largely on electron micrograph images of neutrophils in contact with infected, but not uninfected, hepatocytes undergoing dissolution (18,49,52). In contrast to these data, other studies support the hypothesis that neutrophils mediate resistance to Listeria independently of direct hepatocyte lysis.…”
Section: Neutrophilsmentioning
confidence: 87%
“…Infective foci are neutrophil rich, with the degree of infection proportional to the degree of neutrophilia (3,13,17,18,(43)(44)(45)(46)(47)(48)(49)(50). Depletion of neutrophils in vivo with RB6-8C5 mAb specific for the Gr-1 (Ly-6) cell surface marker demonstrates an early role for these cells in resistance to Listeria infections.…”
Section: Neutrophilsmentioning
confidence: 99%
“…Hepatosplenomegaly, pneumonia and systemic toxicity are all common clinical features of advanced disease in mice. Organisms can be detected within tissue macrophages, neutrophils, dendritic cells (DCs), hepatocytes and type II pulmonary epithelial cells of infected mice (Conlan & North, 1992;Conlan et al, 2003;Bosio & Dow, 2005;Rasmussen et al, 2006;Hall et al, 2007Hall et al, , 2008Bokhari et al, 2008). A recent study by Hall et al (2008) indicated that diverse types of lung cells contain LVS following respiratory challenge in mice.…”
Section: Pathogenesis Of Disease In the Mouse Caused By F Tularensismentioning
confidence: 99%
“…F. tularensis is a faculative intracellular pathogen because it can be cultured in cell-free growth medium as well as inside host cells (Ellis et al ., 2002;Elkins et al ., 2003), but there are no data demonstrating extracellular replication during human or animal infection (Conlan and North, 1992;Fortier et al ., 1994). Thus, F. tularensis may be an obligate intracellular pathogen in vivo , where it has been found to survive and replicate within macrophages, among other cell types (Anthony et al ., 1991;Conlan and North, 1992;Fortier et al ., 1995). Humans can be infected by inhaling as few as 10 F. tularensis , making this one of the most infectious pathogens known (Dennis et al ., 2001;Ellis et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%